Relative Influence of Topology, Dimensionality and Stoichiometry Toward the Properties of Covalent Network Glasses - Lucas, Pierre (Frontiers in Materials, 2019)
Trends in density and fragility are analyzed in the Ge-As-Se, As-Se and Ge-Se system for the purpose of identifying correlation with structural characteristics related to topology, stoichiometry and dimensionality. The Ge-As-Se system provides the most revealing testbed as it permits to isolate individual effects. The fragility of Ge-As-Se glasses is clearly controlled by stoichiometric factors while the topological transition at <r> =2.4 is not observed in this system. The density of Ge-As-Se glasses broadly increase with average coordination but show two anomalies centered near <r> = 2.4 and 2.67. These anomalies merge into a single extremum corresponding to stoichiometric compositions when plotted against excess/deficiency in Se, thereby revealing their common link to stoichiometric factors. Nevertheless, when stoichiometric factors are fixed, dimensional effects are revealed in the form of a linear dependence upon content of tetrahedral Ge. Similarly, a diffuse maximum at the topological transition of <r> = 2.4 is observed when only Se-excess compositions are considered. For the As-Se system, a local maximum in fragility is observed at the two dimensional composition As2Se3, contrary to predictions from topological or stoichiometric factors, thereby indicating that dimensional effect control the fragile behavior. Finally, in the Ge-Se system, a topological transition associated with balance of constraints and degrees of freedom is found at <r> = 2.4 when contributions from stoichiometry and dimensionality are absent. In all system, no case is found where topological effects dominate either stoichiometric or dimensional effects, hence it can be concluded that it is the least predominant contribution while stoichiometry is found to be the prevailing effect.